Modul Pembelajaran untuk Meningkatkan Literasi Agama di Museum Buddha Dhammadasa - Merlin, Eka; Kunatan, Henni; Wulandari, Putri (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
This study aims to develop and disseminate a religious literacy learning module based on the Asian Buddhist Museum Dhammadasa at the Dhammadipa Arama Monastery. The module is designed to enhance visitors' religious literacy by integrating experiential learning methods and constructivist learning approaches. The research employed the Research and Development (R&D) model with a 4D approach (Define, Design, Develop, Disseminate). The development results include a learning module that encompasses exploration, reflection, and evaluation guidelines, supported by interactive technology such as augmented reality (AR). Testing of the module demonstrated a significant improvement in participants' understanding of Buddhist values, such as loving-kindness (metta), compassion (karuna), sympathetic joy (mudita), and equanimity (upekkha), as well as cross-tradition understanding of Buddhism in Asia. This article presents the dissemination of the development results as an effort to support religious moderation and cross-cultural understanding through museum-based learning